Use of St. John's wort in the treatment of mental illnesses - Simões , Deise Vimaana Santos de Souza; Freitas , João Fábio de; Rocha, Samela Goes (Seven Editora, 2024)
This literature review article investigates the use of St. John's Wort as an alternative treatment for mental illnesses. St. John's Wort, also known as St. John's Wort, has been the subject of interest in the field of mental health due to its potentially therapeutic properties. Based on a critical analysis of scientific studies and research, this article explores the role of St. John's Wort in treating psychic conditions such as depression, anxiety, and mood disorder. Essential considerations, including dosages and drug interactions, are discussed to contextualize the safe use of this herb. St. John's Wort presents itself as a complementary treatment option in a scenario where mental health is of increasing importance. DOI:https://doi.org/10.56238/sevened2024.007-082